2013
DOI: 10.1136/jnnp-2012-303520
|View full text |Cite
|
Sign up to set email alerts
|

Is there anything distinctive about epileptic deja vu?

Abstract: Déjà vu is common and qualitatively similar whether it occurs as an epileptic aura or normal phenomenon. However ictal déjà vu occurs more frequently and is accompanied by several distinctive features. It is distinguished primarily by 'the company it keeps'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 15 publications
3
29
0
Order By: Relevance
“…It is considered to be a memory-based illusion resulting from aberrant neural activity among memory-related brain systems, particularly within the medial temporal lobes (MTL; Bartolomei et al 2004;Illman et al 2012;O'Connor and Moulin 2010). Consistent with this notion, the Bdreamy state^reported frequently at the beginning of seizures by patients with medial temporal lobe epilepsy (TLE) often comprises the sensation of inappropriate familiarity characterising DV (e.g., Vignal et al 2007;Warren-Gash and Zeman 2014). Physiological equivalence between the ictal experience of DVand that experienced by healthy individuals remains uncertain, however, and the task now is to understand more precisely the neural events underlying its benign manifestation.…”
Section: Introductionmentioning
confidence: 91%
“…It is considered to be a memory-based illusion resulting from aberrant neural activity among memory-related brain systems, particularly within the medial temporal lobes (MTL; Bartolomei et al 2004;Illman et al 2012;O'Connor and Moulin 2010). Consistent with this notion, the Bdreamy state^reported frequently at the beginning of seizures by patients with medial temporal lobe epilepsy (TLE) often comprises the sensation of inappropriate familiarity characterising DV (e.g., Vignal et al 2007;Warren-Gash and Zeman 2014). Physiological equivalence between the ictal experience of DVand that experienced by healthy individuals remains uncertain, however, and the task now is to understand more precisely the neural events underlying its benign manifestation.…”
Section: Introductionmentioning
confidence: 91%
“…This hypothesis derives from a work studying TLE. It has been shown that the déjà vu experiences of people with and without TLE are phenomenologically similar [85]. This account of déjà vu resonates with historical views of its relation with memory retrieval and consciousness in the temporal lobe (e.g., [87]).…”
Section: The Not-so-strange Sensation Of Déjà Vu In Epilepsymentioning
confidence: 50%
“…This feeling is perhaps more frequent in temporal lobe epilepsy (TLE) where it is reported as an ictal symptom (for review, see [84]). In fact, although patients with TLE who experience déjà vu may do so many times a month [85], the proportion who experience déjà vu is smaller than the proportion of people without epilepsy who experience it (controls 76.1%, TLE 63.1%) [86].…”
Section: The Not-so-strange Sensation Of Déjà Vu In Epilepsymentioning
confidence: 99%
See 2 more Smart Citations